Prevalence of Hemorrhoids Signs and Symptoms among Pregnancies at Maternity Teaching Hospitals in Mosul City - Rana Mohammed Jasim (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: Estimate to the prevalence of hemorrhoids Signs and Symptoms among pregnancies in maternity teaching hospitals in Mosul city. Material: Descriptive study was conducted in maternity teaching hospital 20to30 September 2022 . A purposive sample that consists of (64) patients , chosen according to the criteria . Their age ranges between (15-44) years. A questionnaire was developed for purposive of study & included 3 parts is consist of part one demographic data and part three is composed of (7) items . The overall questions included (28) items. Results: The age groups is between(20-24) years and constituted Prevalence (29.7%), In addition the age groups is between (25-29) years and constituted (29.7%) Most of samples were females constitute of Prevalence (60%) of the total samples. In regard with residence city Prevalence (76.6%) .In regard with levels of education elementary Prevalence (20.3%) .In regard with occupation housewife Prevalence (65.6%) high percentage. Conclusion: This study concluded that the Age, Residence, occupation a variables are the most socio- demographic variables that were associated prevalence of hemorrhoids Signs and Symptoms among pregnancies and the level of education variable.High percent from total sample were in residence city it constitute of Prevalence (76,6%). With regard to the occupation housewife were living urban areas and constitutes Prevalence (65,6%) and there are many high associations among some variables prevalence of hemorrhoids Signs and Symptoms among pregnancies and the age significant. Keywords: Prevalence, Hemorrhoids, Pregnancies.